An annotated catalog of the Iranian Dipsocoromorpha, Enicocephalomorpha, Gerromorpha, Leptopodomorpha and Nepomorpha (Hemiptera: Heteroptera) - Ghahari, Hassan; Moulet, Pierre; Ostovan, Hadi; Linnavuori, Rauno E. (Zootaxa, 2013)
A catalog of aquatic and semiaquatic Heteroptera from Iran is provided based on literature reports and field collections. Representatives of 107 species and morphospecies of the infraorders Dipsocoromorpha, Enicocephalomorpha, Gerromorpha, Leptopodomorpha, and Nepomorpha are listed, and are distributed in 18 families including Aphelocheiridae (1 genus, 1 species), Belostomatidae (1 genus, 1 species), Corixidae (8 genera, 29 species), Dipsocoridae (1 genus, 2 species), Enicocephalidae (2 genera, 2 species), Gerridae (6 genera, 18 species), Hebridae (1 genus, 5 species), Helotrephidae (1 genus, 1 species), Hydrometridae (1 genus, 2 species), Leptopodidae (4 genera, 7 species), Mesoveliidae (1 genus, 2 species), Naucoridae (1 genus, 1 species), Nepidae (3 genera, 5 species), Notonectidae (2 genera, 8 species), Ochteridae (1 genus, 1 species), Pleidae (1 genus, 1 species), Saldidae (5 genera, 14 species), and Veliidae (2 genera, 7 species). Synonyms and geographical distribution of all the species are given, together with an identification key of families. According to the actual catalogs and studies eight species are doubtful for Iranian fauna.